The History of modern fashion from 1850 - Cole, Daniel James; Deihl, Nancy (London Laurence King Publishing, 2015)
This illustrated book looks at the history of fashion from 1850 to 2010. Taking a decade-by-decade approach, Daniel James Cole and Nancy Deihl explore the history of fashion as a lively and dynamic manifestation of 20th-century culture. Covering chronological changes in womenswear, menswear and childrenswear, the book looks at the dissemination of style and the mechanisms of change, at the relationship between fashion and the visual, applied and performing arts, the intertwined relationship between fashion and popular culture, the impact of new materials and technology and the growing globalization of style.
1850-1890: the dawn of modern clothing -- The 1890s: extremes of the Gilded Age -- The 1900s: a new century -- The 1910s: exotic fantasy, wartime reality -- The 1920s: les années folles -- The 1930s: aspirations of glamour -- The 1940s: war and recovery -- The 1950s: couture opulence, suburban style -- The 1960s: fashion for the future -- The 1970s: revivals and individuality -- The 1980s: power dressing and postmodernism -- The 1990s: subcultures and supermodels -- The 2000s: mixed messages.
Includes bibliographical references (pages 468-473) and index.
Keywords: Fashion; Fashion -- History -- 19th century; Fashion -- History -- 20th century; Fashion -- History -- 21st century